Re-conceptualizing English Language Education through Autobiography: Toward a Pedagogy of Humiliations and Humanness - Jennifer-Lynn Bene (Canadian Journal for New Scholars in Education, 2008)
This paper considers how English language educators might use autobiography as a pedagogical form to engage their multiple experiences and relations to English and Englishness, and to consider implications for their work. Reflecting on autobiography from this perspective offers possibilities for grappling with our multiple connections and dis-connections to English and Englishness, becoming conscious of the discourses which shape us as educators, and engaging difference in productive and meaningful ways. In undertaking autobiography, we face aspects of ourselves, often aspects that come into conflict. This process of dis-equilibrium has the potential to engender a shift in understanding that helps us to re-conceptualize normative constructions and representations of English language pedagogy. This is a necessary undertaking for educators attempting to work with/in the possibilities of engaging reflectively and critically in English language education. It also offers a space to consider how we might use English ‘appropriately’ in our teachings and engagements.